Listening strategies employed by non-English department students - Gestanti, Rohfin Andria (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2017)
Language learning strategy is one of the influential aspects for studentsâ success in learning a language. Basically, language learning strategies are closely related to students taking language-related department. However, students from non-English Department also have the indication of using the strategies since English is one of the subjects taught in the curriculum. Thus this study aims to (1) identify what strategies are used by non-English Department students in Listening class and (2) describes to how the use of strategies influence students listening achievement. This study is a qualitative descriptive study with second-semester students from Governmental Science Department as the research subject. A questionnaire, observation, and documentation are used to collect the data. After analyzing the data, it was found that some strategies are used by non-English department students in their Listening subject, namely memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies. Moreover, the students use those strategies in moderate level. Thus, a comparison between the level of strategies use and studentsâ listening scores is made to describe to what extends the use of strategies influence studentsâ achievements.